The indebtedness and over-indebtedness of children and adolescents: causes, consequences and prevention options - Krušinská, Kristýna (Advances in Social Sciences Research Journal, 2014)
The objective of this paper is to call attention to the fact that the issue of indebtedness and over-indebtedness needs to be addressed with regard to people who are still minors. First of all, the current perception of this topic is described, along with the most common myths that one can encounter. Subsequently, the most common causes of the indebtedness of children and adolescents are mentioned as well as its possible consequences. The conclusion is devoted to the issue of the prevention of indebtedness and over-indebtedness in this group, and the roles that social workers can play and the courses of action they can select. This paper is based mainly on the experience the author gained while working at the Citizens Advice Bureau REMEDIUM, which provides debt consultancy and also conducts seminars and courses on the topic of debt prevention for children and adolescents as well as for teachers and social workers.